Neural correlates of creative writing: An fMRI Study - Shah, Carolin (Hum Brain Mapp, 2011)
Cerebral activations involved in actual writing of a new story and the associated correlates with creative performance are still unexplored. To investigate the different aspects of the creative writing process, we used functional magnetic resonance imaging while 28 healthy participants performed a new paradigm related to creative writing: “brainstorming” (planning a story) and “creative writing” (writing a new and creative continuation of a given literary text), as well as an additional control paradigm of “reading” and “copying.” Individual verbal creativity was assessed with a verbal creativity test and creative performance with a qualitative rating of the creative products. “brainstorming” engaged cognitive, linguistic, and creative brain functions mainly represented in a parieto‐frontal‐temporal network, as well as writing preparation, and visual and imaginative processing. “creative writing” activated motor and visual brain areas for handwriting and additionally, cognitive and linguistic areas. Episodic memory retrieval, free‐associative and spontaneous cognition, and semantic integration were observed in a right lateralized activation pattern in bilateral hippocampi, bilateral temporal poles (BA 38), and bilateral posterior cingulate cortex in a “creative writing” minus “copying” comparison. A correlation analysis of “creative writing” minus “copying” with the creativity index revealed activation in the left inferior frontal gyrus (BA 45) and the left temporal pole (BA 38). Thus, verbal creativity during “creative writing” is associated with verbal and semantic memory as well as semantic integration. Hum Brain Mapp, 2013. © 2011 Wiley Periodicals, Inc.